Code Mixing Used in Students’ Conversation in Informal Setting - Jajat Imanudin (Universitas Islam Al-Ihya Kuningan, 2021)
The writer is interested to do a study on code mixing used in informal conversation done by the students. This study is conducted to identify code-mixing indicators used by the students in informal setting. There were some indicators in using code-mixing in a conversation. However, a sentence is not contained all the indicators. The method used in this study was descriptive method. The population used in this study is the informal conversation setting of the second year students and took ten informal conversation setting of English Education Department Universitas Islam Al-Ihya Kuningan. the writer used transcripts known as recording and transcribing using these following procedure: a) determining the objectives; b) determining the population and samples; c) recording the data from the samples; d) transcribing the data; e) analyzing the transcript and f) drawing conclusion. From the data gained, the researcher found that code mixing used in informal conversation indicates that there is no priorities one language in certain time. In this case, the use of code mixing is a media for students in improving their speaking ability.